Seismic processed data (Ocean Bottom Seismometer working area dataset, profile P100) during RRS JAMES COOK cruise JC228, Guatemala Basin, North Pacific Ocean - Grevemeyer, Ingo; Henstock, Timothy J; Dannowski, Anke (PANGAEA, 2025)
The data comprise processed active-source seismic data acquired with ocean bottom seismometer (OBS) along profile p100. The data were collected in the Guatemala Basin of the Eastern Pacific Ocean during the joint German/British expedition JC228 of the research vessel RRS JAMES COOK in December of 2022. The data set consists of 12 OBS stations deployed at an interval of 7 km receiving shots of a tuned 5000 cubi-inch airgun array, fired at 90 s interval, along a 115 km long profile. The seismic line crosses Ocean Drilling Program Hole 1256D. Each OBS consists of 4 channels (channel 1: hydrophone; channel 2: horizontal component 1; channel 3: horizontal component 2; channel 4: vertical component).
Keywords: OBS; ocean bottom seismometer; oceanic crust; Pacific Ocean; Seismic wide-angle reflection and refraction data